P2P Shariah Lending in the Perspective of Fiqh al-Mu'amalat al-Maliyah: Analysis of Sharia Compliance, Regulatory Challenges, and Maqasid al-Shari'ah in Fintech Lending in Indonesia - Hanifa Aulia; Muhammad Ariful Ma'arif (Cv. Kayaswara, 2026)
Sharia-based peer-to-peer (P2P) lending has grown rapidly as an alternative to Islamic financial services that promise financial inclusion for people who have not been served by conventional or sharia banking. However, the growth of sharia P2P lending platforms presents significant challenges related to compliance with the principles of fiqh al-mu'amalat al-maliyah, operational scalability, and building trust among stakeholders. This study aims to comprehensively analyze the Islamic legal framework that governs sharia P2P lending in Indonesia, including its conformity with maqasid al-shari'ah, as well as examine the regulatory challenges and trust mechanisms applied to promote equitable financial inclusion. Using a qualitative approach through a systematic literature review based on the PRISMA protocol, this study examined 45 scientific articles published between 2018–2025 from the Scopus database, Web of Science, and Google Scholar. The findings show that there are four main dimensions of challenges: (1) the fiqh muamalat framework that requires adaptation to the sharia P2P lending business model, especially related to the prohibition of riba, gharar, and maysir; (2) a regulatory framework that has not fully integrated sharia principles; (3) trust mechanisms that rely on data transparency, platform reputation, and consumer protection in accordance with maqasid al-shari'ah; and (4) limited digital infrastructure in remote areas that hinder scalability. This study concludes that synergy between regulators, the National Sharia Council (DSN-MUI), sharia P2P platforms, and the community is needed to build a sustainable, inclusive, and sharia-compliant sharia P2P lending ecosystem. Practical implications include policy recommendations for the Financial Services Authority (OJK) and DSN-MUI as well as strategies for developing trust mechanisms based on Islamic values.